Kemiskinan ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI KABUPATEN SRAGEN: Kemiskinan merupakan kondisi di mana seseorang tidak dapat menikmati segala macam pilihan dan kesempatan dalam pemenuhan kebutuhan dasarnya, seperti tidak mendapatkan standar hidup yang layak, kebebasan, harga diri dan rasa dihormati seperti orang lain, serta suramnya masa depan. Penelitian ini bertujuan untuk meneliti faktor-faktor yang mempengaruhi tingkat Kemiskinan di Kabupaten Sragen periode tahun 20 - Masitha Bella Amalia (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2023)
Poverty is a condition in which a person cannot enjoy all kinds of choices and opportunities in fulfilling his basic needs, such as not getting a decent standard of living, freedom, self-esteem and a sense of respect like other people, and the dismal future. This study aims to examine the factors that influence the level of poverty in Sragen Regency for the period 2005-2020, using Ordinary Least Square (OLS) regression analysis on time series data. The results shows that the Gross Regional Domestic Product has not been effective in reducing the poverty rate, the minimum wage has been effective in reducing the poverty level, while the number of people participating in the family planning program has not been effective in reducing the poverty rate. The Sragen Regency Government should seek equal distribution of income so that economic growth is optimal in reducing poverty. The minimum wage must continue to be increased every year, adjusted to the increase in the cost of living of workers so that people's purchasing power is maintained or increased, to protect workers from falling into poverty. The government must improve the family planning program so that it is not only oriented towards reducing the rate of population growth, but also pays attention to the welfare of the families of family planning participants.